2021
DOI: 10.3390/su13179524
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Workers’ Physical Activity and Sedentary Behavior during the COVID-19 Pandemic

Abstract: Background: COVID-19 has changed the world and strongly affected the health of the people and the quality of their life. These changes might impact employees’ physical activity (PA) and sedentary behavior (SB). This study aimed to summarize the literature focusing on the COVID-19-caused changes in physical activity and sedentary behavior among the adult working population. Methods: Literature searches were conducted in June 2021 using multiple electronic databases. The following keywords and synonyms were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 96 publications
(139 reference statements)
5
45
1
1
Order By: Relevance
“…We estimated the physical activity as time spent; counting the steps; the percentage of the sample; comparison with pre-pandemic IT workers. These results are similar to other studies that showed a decreased level of physical activity [ 28 , 29 ]. Besides the reduction in PA, the study revealed an increased time in sedentary behaviors, like working at the computer.…”
Section: Discussionsupporting
confidence: 92%
“…We estimated the physical activity as time spent; counting the steps; the percentage of the sample; comparison with pre-pandemic IT workers. These results are similar to other studies that showed a decreased level of physical activity [ 28 , 29 ]. Besides the reduction in PA, the study revealed an increased time in sedentary behaviors, like working at the computer.…”
Section: Discussionsupporting
confidence: 92%
“…The implementation of preventive measures, such as social distancing, shelter-inplace, and work-from-home, have limited daily activities and in-person interactions. A recent review focusing on physical activity and sedentary behavior during the COVID-19 pandemic among employed adults reported consistent evidence of decreased overall physical activity levels and increased total sedentary behaviors across most of the studies from various countries [10]. Benefits of physical activity in preventing or treating depression have been shown in both observational and experimental studies [11].…”
Section: Variables Related To Depression During the Pandemicmentioning
confidence: 99%
“…A number of studies have revealed that physical activity decreased and sedentary behavior increased among all age groups during the COVID-19 lockdown. 6 , 7 , 17 The results of this study revealed that many workers became physically inactive and gained weight even though a lockdown has never been imposed in Japan. Many companies introduced remote working with the COVID-19 pandemic as a trigger.…”
Section: Discussionmentioning
confidence: 77%
“…This study provides evidence for the impact of COVID-19 pandemic on workers’ health. Decreased physical activity and increased weight gain during the COVID-19 pandemic are important issues in most countries including Japan 6,,17 . The results of this study can provide valuable information for planning health promotion programs in the COVID-19 era.…”
Section: Discussionmentioning
confidence: 83%